Fiume Po (1966): la nascita di un progetto di Cesare Zavattini e William M. Zanca - Criscione, Miryam (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
Based on documents held in the Cesare Zavattini Archive in Reggio Emilia, this essay analyzes the conception and development of Fiume Po, a 1966 photobook with texts by Zavattini and photographs by William M. Zanca. Particular attention is given to the relationship between words and images created by the book’s layout and to the broader cultural debate on the social function of the photobook among photographic critics of the 1950s and 60s.